Acute gross painless transudative ascites in a patient with lupus. (17th January 2014) - Erfani, T; Manolios, N; Howe, G; Spencer, D
Abstract : Gross ascites is a rare presentation of lupus. Ascites in lupus may be due to lupus peritonitis or secondary to one of the complications including nephrotic syndrome. The ascites due to lupus peritonitis has been described as exudative with a serum-ascites albumin gradient (SAAG) below 11 g/L, unless associated with nephrotic syndrome. We report an unusual case of lupus ascites in a 23-year-old woman who presented with acute painless gross ascites with no constitutional, skin or musculoskeletal symptoms of a lupus flare. The ascites was a transudate with SAAG above 11 g/L with no associated nephrotic syndrome. She was treated with corticosteroids, mycophenolate mofetil and diuretics with a good response and no recurrence of her ascites.